Worker trapping: a sustainable management tool for invasive social wasps? - Melo, Romina Ayelen Luz (2024)
The invasive social wasp Vespula germanica is a harmful pest, mainly in urban environments. Despite extensive research on ecology and control, there are currently no effective, sustainable strategies to manage populations in the invaded range. We evaluated the effects of worker trapping on V. germanica abundance and nest activity in Southern Argentina. During two consecutive years, a high-density trapping was deployed in four plots of one hectare each. The procedure consisted of placing 25 non-toxic meat-baited traps, creating a grid of 5 × 5 traps for 4 weeks. Worker wasp abundance and the traffic rate of all the nests in the plots were measured 1 week before and one after trapping. Our results showed that worker catches resulted in a 65% reduction in local wasp abundance and a 48% in traffic rate of nests within the treated area. Similarly, a decrease in wasp abundance was obtained one year after trapping. Employing worker trapping as a tool could prove useful and environmentally friendly in reducing local wasp abundance during peak activity.